OJK’s Authority after Law No. 4/2023: A Legal Certainty Perspective - Sushanty, Vera Rimbawani (Equality : Jurnal Hukum dan Keadilan, 2025)
The financial services sector, which is one of the main pillars in people's lives, has experienced rapid development. However, this progress also brings various challenges, especially related to fundamental problems in the financial sector. Financial problems in society are increasingly diverse so that the law is required to be more adaptive in responding to these problems considering that the law is basically a reflection of the will of the community. Strengthening the role of the Financial Services Authority (OJK) after the enactment of Law Number 4 of 2023 concerning the Development and Strengthening of the Financial Services Sector (UU P2SK) which includes provisions that every action and decision taken by OJK based on the law cannot be used as an object of lawsuit in state administration. This provision has a direct impact on the financial services industry and society, especially if OJK's decision has negative consequences for them. This study aims to analyze the impact of the P2SK Law on national and state life, especially in relation to the duties and functions of OJK. To achieve this goal, this study uses a literature study method to examine various views related to legal doctrines that affect financial institutions. The results of the study indicate an expansion of OJK's supervisory duties and functions, especially in the field of digital finance and education for the public. This expansion of authority is a challenge for OJK to play a role as a solution in overcoming various financial problems that occur in society.